Digital and/or Analogue? : Notes on the Exhibition Display from Post Zang Tumb Tuum. Art Life Politics: Italy 1918-1943 to 1923: Past Futures - Maiorino, Massimo (Mimesis Journal, 2024)
The museum, and in particular the field of temporary exhibitions, has become a space for experimentation, a laboratory for verifying the digital horizon as a medium of narration of art history. This condition is evident in two exhibitions in Milan: Post Zang Tumb Tuuum. Art Life Politics: Italia 1918-1943 at the Prada Foundation (2018) and 1923: Past Futures at the Milan Triennale (2022), that highlight the convergence and the difference between analogue writings and digital devices. The article analyses these exhibitions as possible paradigms of the exhibition and museum canon of the present time in relation to digital humanities.